Answer:
18:6
Step-by-step explanation:
3 + 1 = 4
24 ÷ 4 = 6
3 x 6 = 18
6 x 1 = 6
Answer:
2x-1=y
Step-by-step explanation:
You currently have y=2x-1 in y=mx+b form.
All we have to do is reorganize the terms into: mx+b=y
Answer: 335
Step-by-step explanation:
A = l × w. Substitute 72 into A and fill in the rest of the equation.
w = l - 1. Plug l - 1 into w
72 = l × (l - 1). Multiply l by (l - 1)
72 = l^2 - l. Subtract 72 from each side.
0 = l^2 - l - 72. Factor.
0 = (l + 8) (l - 9). Set each term equal to zero.
(l + 8) = 0. Subtract 8 from each side.
l = -8. Length cant be a negative number so let's try the other term.
(l - 9) = 0. Add 9 to each side.
l = 9. The length is 9.
Earlier we stated that the width is one less than the length, therefore, the width is 9 - 1 = 8.
The width is 8 units.
Answer:
Step-by-step explanation:
1 dined esta Ricardo
2donde vamos
3que class de gusta mas
4que ensena el profesor
5como son Los estudiantes